Polysaccharides from marine resources exhibit great potential in the treatment of tumor: A review - Hao Ju; Chong Yu; Wei Liu; Hai-Huang Li; Ze Fu; Yan-Chao Wu; Pi-Xian Gong; Hui-Jing Li (Carbohydrate Polymer Technologies and Applications, 2023)
Tumor refers to the neogrowth formed by the hyperplasia of local tissue cells under various tumor factors. Because this new creature mostly appears in a lump -like protrusions, also known as neoplasm. Relevant investigation shows that millions of new tumor cases and millions of tumor deaths occur every year. Although tumor treatments such as surgical resection, chemotherapy, radiotherapy, immunotherapy, endocrine therapy, and gene therapy can inhibit tumors to a certain extent, they also have a variety of shortcomings, such as poor drug targeting, expensive prices, serious toxic side effects, and limited efficacy. It is necessary to overcome the shortcomings of existing treatment strategies. Therefore, there are urgent needs for safe and effective new drugs to treat tumor. Marine polysaccharides have a wide range of sources, mainly including seaweed polysaccharides, marine animal polysaccharides and marine microbial polysaccharides. With the deepening of antitumor mechanism of marine polysaccharides, it is believed that marine polysaccharides may play an antitumor role by inhibiting tumor angiogenesis, inducing tumor cell apoptosis, scavenging free radicals, and activating the immune system. By referring to the literatures in recent 3 years, the antitumor effect and mechanism of marine polysaccharides were reviewed in order to provide reference for clinical medication.